Low-intensity pulsed ultrasound promotes cell viability and inhibits apoptosis of H9C2 cardiomyocytes in 3D bioprinting scaffolds via PI3K-Akt and ERK1/2 pathways. (September 2022) - Hu, Yugang; Jia, Yan; Wang, Hao; Cao, Quan; Yang, Yuanting; Zhou, Yanxiang; Tan, Tuantuan; Huang, Xin; Zhou, Qing
The aim of this study was to investigate whether low-intensity pulsed ultrasound (LIPUS) promotes myocardial cell viability in three-dimensional (3D) cell-laden gelatin methacryloyl (GelMA) scaffolds. Cardiomyoblasts (H9C2s) were mixed in 6% (w/v) GelMA bio-inks and printed using an extrusion-based 3D bioprinter. These scaffolds were exposed to LIPUS with different parameters or sham-irradiated to optimize the LIPUS treatment. The viability of H9C2s was measured using Cell Counting Kit-8 (CCK8), cell cycle, and live and dead cell double-staining assays. Western blot analysis was performed to determine the protein expression levels. We successfully fabricated 3D bio-printed cell-laden GelMA scaffolds. CCK8 and live and dead cell double-staining assays indicated that the optimal conditions for LIPUS were a frequency of 0.5 MHz and an exposure time of 10 min. Cell cycle analysis showed that LIPUS promoted the entry of cells into the S and G2/M phases from the G0/G1 phase. Western blot analysis revealed that LIPUS promoted the phosphorylation and activation of ERK1/2 and PI3K-Akt. The ERK1/2 inhibitor (U0126) and PI3K inhibitor (LY294002) significantly reduced LIPUS-induced phosphorylation of ERK1/2 and PI3K-Akt, respectively, which in turn reduced the LIPUS-induced viability of H9C2s in 3D bio-printed cell-laden GelMA scaffolds. A frequency of 0.5 MHz and exposure time of 10 min for LIPUS exposure can be adapted to achieve optimized culture effects on myocardial cells in 3D bio-printed cell-laden GelMA scaffolds via the ERK1/2 and PI3K-Akt signaling pathways.